HUBUNGAN PERSEPSI SISWA TERHADAP PENGGUNAAN MEDIA DAN PERAN ORANG TUA DENGAN HASIL BELAJAR TAHFIDZUL QURAN DI SDIT AT TAQWA NAROGONG,BEKASI - Fadillah Prabowo; Khairan M Arif (Akademika, 2016)
The research is aimed to analyze 1 ) Correlation to the Use of Media Student Perceptionswith Tafidzul Quran Study Result, 2 ) Correlation between the Role of Parents with TahfidzulQuran Study Result, 3 ) Correlations between Student Perceptions of the Use of Media and theRole of Parents with the Tahfidzul Quran Study Result.This study used a survey method using correlation techniques . The population in thisstudy was student class IV to class VI SDIT AT Taqwa Narogong Bekasi city , amounting to 101people . Based on the population , obtained a sample of 50 people .Results show : 1 ) there is a positive and significant relationship between students'perceptions of the use of the media with study result. The coefficient of correlation obtained is0.522 . Regression equation obtained is Ŷ = 12.426 + 0.063 X1 . 2 ) there is a positive andsignificant relationship between the roles of parents with study result . The coefficient ofcorrelation obtained is 0.593 . Regression equation obtained is Ŷ = 11.660 + 0.078 X2 . 3 ) thereis a positive and significant relationship between students' perceptions of the use of media andthe role of parents with Tahfidzul quran study result . The coefficient of correlation obtained is0.658 . Regression equation obtained is Ŷ = 10.235 + 0.039 X1 + 0.059 X2.The conclusion of this research that there is a positive and significant correlation betweenpercepti students to the use of media and the role of parents with tahfidzul quran study result.The results of this study have implications on the improvement of tahfidzul quran study result.Tahfidzul quran learning outcomes can be improved through increased use of instructionalmedia and the increasing role of parent